Hubungan Monitoring Dengan Kepatuhan Perawat Dalam Pencegahan Infeksi Nasokomial - Elida Pakpahan; Weslei Daeli; Bambang Suryadi (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Introduction. Health care-associated infectious diseases or Healthcare Associated Infections (HAIs) in hospitals are a serious problem because they threaten the health and safety of patients and health workers. The duties and responsibilities of Infection Prevention and Control (PPI) include supervising and monitoring the implementation of the PPI program, complying with the implementation of SOPs and providing suggestions for improvement. Objective. To determine the relationship between PPI monitoring and the level of nurse compliance in preventing nasocomial infections at Tebet Hospital. Method. Using quantitative correlational with a cross sectional approach with a total of 45 respondents and total sampling technique. Results. It was found that there was a relationship between monitoring infection prevention and control (PPI) and nurses' compliance in preventing nasocomial infections at Tebet Hospital. It was found that bivariate analysis using the chi-square test obtained a p-value 0.026. In conclusion, there is a relationship between monitoring infection prevention and control (PPI) and nurses' compliance in preventing nasocomial infections. Suggestions to nurses can increase nurses' compliance in implementing nasocomial infection prevention in accordance with standard operational procedures.